Pengaruh Kompetensi Sumber Daya Manusia dan Sistem Pengendalian Internal Pemerintah Terhadap Kualitas Laporan Keuangan - Nita Ayu Trisnawati; Arie Apriadi Nugraha; Sudjana (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
Abstract: Financial reports are a medium to account for the performance of the government to users of financial statements, especially to the public. Financial reports must produce quality and relevant information, one of the factorssthat affecttthe qualityzof financial reports is seen from their preparation by competent human resources.and also the internallcontrol..system of the organization is well maintained. Inn this case, the competence of HR has the effect of creating an information value in the financial statement entity that affects its quality. Cimahi City has received a WTP opinion for financial statements, but there are still some notes, one of which is the limited human resources that have qualifications in economic education, especially accounting. In addition, there are problems with the Government's Internal Control System in Cimahi City, namely according to the SPIP element, Cimahi City is still lagging behind other regions in West Java due to the implementation of activities and programs that are not appropriate at the beginning. This studycaims to determine the effecttof Human Resource Competence (HR) and GovernmentzInternallControllSystem (SPIP) onzthezQualityzofzFinancial Reports in the Cimahi City Government. The population of this study was 27 RegionalsApparatussOrganizational Units (SOPD) located in the Cimahi City Government, and the sample taken was the entire population. The type of this research is quantitative, the data is obtained by questionnaire, the respondents are taken as many as 76 respondents with techniques using statistical tools IBM SPSS Version 26 and using multiplezlinearzanalysis. Basedzon thezresults of the study, the two variables, namely the competencee of human resourcesxand the government's internal control system havexa positive and significant effect of 53.4% Keywords: Human Resources Competence, Government Internal Control System, Quality of Financial Statements